Influence of Staphylococcus Aureus on the Oral Candida Albicans - Mouna Akeel Hamed Al-Oebady (Journal of Global Pharma Technology, 2016)
Candida albicans is that the most current isolated from the human body and it consider as a natural part of the commensal microorganisms. The mouth is colonized by many of bacterial species, and it also the relationship between these oral bacteria and C. albicans has been a subject of interest in understanding the event of candidiasis. Many studies have tried to explain the bacteria-fungal relationship within the oral environment; however, few have targeted on the single bacterial species inhibiting growth of C. albicans. Staphylococcus aureus and Candida albicans were isolated and purified from the samples of 50 patients with the fixed orthodontic appliances and PCR was performed to identify this isolated. The microscopic examination and qPCR were carried out to determine the inhibitory impact of S. aureus on C. albicans. This study demonstrated Staphylococcus aureus displayed the strongest inhibitory effect on the growth of Candida albicans. By qPCR assay, all isolated C. albicans were inhibited on the growth by S. aureus in the various periods. Mixed culture experiments also demonstrated inhibitory of C. albicans by S. aureus.Keywords: PCR, Staphyloccous, Candida, Oral cavity.